Rethinking umbrella clauses in international investment agreements - Julien Chaisse (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
This Perspective probes the complexities of umbrella clauses in international investment agreements, spotlighting their inherent legal ambiguities and potential for misuse. It advocates for careful negotiation and refinement of these clauses or, alternatively, their elimination to ensure clearer, more predictable investment frameworks.
Keywords: 330